(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Without a doubt, technology is a gift for every aspect of the life. In past centuries, technology did not exist at all. For example, people didn’t know what technology or the internet was. By the end of the twentieth century, the word “technology” spread first in foreign countries and then in Uzbekistan. At the beginning of twenty-first century, the term technology is being used all over the world. In our rapidly changing world, technology has developed all over the world. Nowadays, more and more people, even young children know what the Internet is and how to use it. That is why, technology plays an important role in everyone’s life at the current time. Actually, technology has revolutionized the field of education. The importance of technology at schools and at universities can’t be ignored. Because of technology, such as computers and mobile phones it is easier for teachers to impart knowledge and for students to acquire it in education. Definitely, the use of technology has made the process of teaching and learning all more enjoyable.